On Selected Aspects of Using AI in Teaching Czech as a Foreign Language - Hradilová, Darina; Kij, Jan (Bohemistyka, 2026)
This paper focuses on the possibilities of employing generative artificial intelligence (AI) in teaching Czech as a foreign language. Since only a limited number of studies have so far been published on the integration of AI into Czech language instruction, this text focuses primarily on international experience with incorporating AI into foreign language education. This study takes the form of a case study with the objective of determining whether, and in what ways, students may achieve better results through the use of AI than when working with traditional sources; how they employ AI when performing tasks aimed at developing lexical and grammatical competence and productive writing skills; and whether or not teachers are able to detect the use of AI in students’ work. The data on which this study is based was collected within an experiment conducted amongst selected students and teachers participating in the Summer School of Slavonic Studies at the Faculty of Arts, Palacký University Olomouc.